Documentation as Group Activity: Performing the Fluxus Network. (1st October 2016) - Santone, Jessica
Abstract : Among the artists affiliated with the international performance and intermedia group Fluxus, documentation was important for the circulation of ideas to participants around the world. In many cases, participation in actuality was less open-ended and rather constrained through the invitation of like-minded acquaintances. Gathering participants' documents together in publications, films, and other media projects following a collaborative action thus provided occasions for a diverse group of artists to share details about their personal or social attributes as much as they also provided records of activity or interpretation. This article discusses examples of documentation in Fluxus as both process and system, where the social dimensions of the Fluxus network were most clearly visible. Documenting was not simply a means of sharing ephemeral acts or inviting collaboration, but was essential to the subtle politics of the group's work. As performance of the network, documentation in Fluxus conveyed the group's shared values of heterogeneity and resistance to normalizing Cold War era bureaucracies.